Panchromatic ternary/quaternary polymer/fullerene BHJ solar cells based on novel silicon naphthalocyanine and silicon phthalocyanine dye sensitizers. Issue 6 (12th December 2016) - Ke, Lili; Gasparini, Nicola; Min, Jie; Zhang, Hong; Adam, Matthias; Rechberger, Stefanie; Forberich, Karen; Zhang, Chaohong; Spiecker, Erdmann; Tykwinski, Rik R.; Brabec, Christoph J.; Ameri, Tayebeh
Abstract : SiNC-1 is successfully applied in ternary/quaternary devices, accompanied by charge transfer/transport mechanism studies. Abstract : More efficient light harvesting throughout the whole solar spectrum by introducing third and fourth components offers a new pathway towards the development of high efficiency organic solar cells based on polymer/fullerene blends. Recently, dye molecules have been utilized as promising light harvesting photosensitizers in the near-IR region. Herein, we report the design, synthesis and application of a novel silicon naphthalocyanine (SiNC-1 ) as an efficient photosensitizer in single dye ternary devices as well as in multi-colored co-sensitized quaternary devices, incorporating a silicon phthalocyanine (SiPC-0 orSiPC-1 ) as the fourth component to complement the spectral absorption of theSiNC-1 . The dominant complex charge transfer/transport mechanism behind the enhanced photosensitivity of the ternary blend has been investigated by means of electrical, optical, and advanced characterization techniques. External quantum efficiency (EQE) measurements on multi-colored dye sensitized devices covering the UV-vis as well as near-IR regions from 350 up to 900 nm outline apparent signal characteristics of each single dye, corroborating the effective contribution of bothSiPC andSiNC dyes to enhancing the short-circuit current density ( J SC ). Our results further illustrate the potential of the multi-colored dye sensitization concept as a powerful approach to mitigate the non-ideal optical absorption normally encountered in organic-based optoelectronic devices.